Multicultural Islamic Education: Innovation in Strengthening Tolerance in Secondary Schools - Achmad Abdul Cholik; Miftahul Jannah (LP3M Pascasarjana STAI Ibnurusyd, 2025)
This study aims to describe the practice and design an innovative model of multicultural Islamic education in an effort to strengthen the values ​​of tolerance in secondary schools. In the context of a multicultural Indonesian society, Islamic education must be able to internalize the values ​​of diversity and strengthen the character of tolerant and moderate students. This study uses a qualitative approach with a descriptive-constructive study type, which is conducted through observation, in-depth interviews, and documentation in several secondary schools. The results of the study indicate that a learning approach that integrates multicultural values ​​into Islamic education can create an inclusive learning atmosphere, strengthen students' empathetic attitudes, and minimize symptoms of intolerance. The innovative model developed in this study includes the formulation of a contextual curriculum, active learning methods, the use of multicultural digital media, and the involvement of teachers as facilitators and role models of tolerant attitudes. With the support of an open school environment and inclusive policies, this model is considered effective and applicable in shaping the character of students who are able to live harmoniously in a diverse society.